Extensive and persistent tongue ulceration is an early character of dyskeratosis congenita - Xuefeng Zhang; Hongxia Dan; Yu Zhou; Wanxin Sun; Wanchun Yang; Xin Zeng (Orphanet Journal of Rare Diseases)
Abstract Background Dyskeratosis congenita (DC) is a rare and fatal disease, presenting with a classic triad of skin pigmentation, nail dystrophy and oral leukoplakia. However, diagnosing DC is challenging based solely on the protean manifestations and multisystemic involvement. Therefore, it is urgent to identify an early feature facilitating initial suspicion of DC. Results In this study, we enrolled a cohort of six male children diagnosed with DC, all of whom exhibited erosions or ulcers on the tongue, while five of them did not display the complete classic triad. Strikingly, oral erosions or ulcers have never been included in any existing clinical diagnostic criteria for DC. Through a retrospective analysis, we further demonstrated that extensive and persistent tongue ulceration emerges as an early and practicable clinical marker, provoking suspicion of DC even in the absence of the classic triad. Conclusions Our findings challenge prevailing diagnostic criteria and advocates for an expanded consideration of tongue ulceration as a primary and indicative manifestation of DC, thereby affording a strategic advantage for early detection and intervention of this lethal disease.